Involvement of The Actors in Conversion Control of Agricultural Land (Case Study in Tabanan District, Bali Province) - ., Widhianthini; Dharmawan, Arya Hadi; Azam Achsani, Noer (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTThe purpose of this research is to know how the role of government actors, private or investors and indigenous institutions (Subak and Pakraman) in the management of land resources (including water) so that the conversion of agricultural land can be prevented. The study was conducted in Tabanan, Bali Province. Depth interview techniques and stakeholder analysis as an approach of this research. A stakeholder analysis is instrumental to understand the social and institutional context of a program or project activities. The purpose of stakeholder analysis is to determine interests and their authority in preventing the conversion of agricultural land. The results showed that there are two forces actors (stakeholders) in the management of land resources (including water). The government in collaboration with investors and has a role as a player, while Subak and Pakraman have a role on the position of the object. Power relations are played by actors of government is still dominant compared to indigenous institutional Subak and Pakraman. Investors who have the capital strength and enthroned as the ‘king’ always pave the spatial plannings are on ‘profit-seeking’ biggest for himself. Power is seen as a mechanism of domination which is a form of power against the other in a relationship dominated by dominated or powerfull by the powerless. The duality of land governance (including water) between actors is the dualism solution. The duality that lies in the fact, that he could be seen as rules that a principle for action in a wide range of space and time, while it is the result (outcome) and means looping action thus overcoming space and time. Duality of land governance (including water) shows that in the future that is necessary is to put Subak and Pakraman in a position of political strength parallel to desa dinas and other government institutions.Keywords: indigenous institutions (Subak, Pakraman), conversion of agricultural land, stakeholder analysis, duality of land governanceABSTRAKTujuan dari penelitian ini adalah mengetahui bagaimana peran aktor pemerintah, swasta atau investor, dan kelembagaan lokal (subak dan desa pakraman) dalam pengelolaan sumber daya lahan (termasuk air) sehingga konversi lahan pertanian dapat dicegah. Penelitian dilakukan di Kabupaten Tabanan, Propinsi Bali. Teknik wawancara yang mendalam dan analisis stakeholder sebagai pendekatan penelitian ini. Analisis stakeholder merupakan instrument untuk memahami konteks social dan kelembagaan dari program atau kegiatan proyek. Tujuan dari analisis stakeholder adalah untuk menentukan minat dan kewenangan mereka dalam mencegah konversi lahan pertanian. Hasil memperlihatkan bahwa terdapat dua kekuatan aktor (stakeholder) dalam pengelolaan sumberdaya lahan (termasuk air). Pemerintah berkolaborasi dengan investor dan memiliki peran sebagai pemain, sedangkan subak dan desa pakraman memiliki peran pada posisi objek. Relasi kuasa yang dimainkan oleh aktor pemerintah masih bersifat dominan dibandingkan kelembagaan lokal subak dan desa pakraman. Aktor investor yang memiliki kekuatan modal dan bertahta sebagai ‘raja’ selalu melicinkan perencanaan-perencanaan tata ruang yang memberikan ‘profit seeking’ terbesar bagi dirinya. Kekuasaan dipandang sebagai mekanisme dominasi yang merupakan bentuk kekuasaan terhadap yang lain dalam relasi yang mendominasi dengan yang didominasi atau yang berkuasa dengan yang tidak berdaya. Dualitas tata kelola lahan (termasuk air) antar para aktor merupakan pemecahan dualism tersebut. Dualitas itu terletak dalam fakta, bahwa ia bisa dipandang sebagai aturan yang menjadi prinsip bagi tindakan di berbagai ruang dan waktu, sekaligus ia merupakan hasil (outcome) dan sarana perulangan tindakan yang karenanya mengatasi ruang dan waktu. Dualitas tata kelola lahan (termasuk air) ini menunjukkan bahwa kedepan yang diperlukan adalah menempatkan subak dan desa pakraman pada posisi kekuatan politik yang sejajar dengan desa dinas dan kelembagaan pemerintah lainnya.Kata kunci: kelembagaan lokal (subak, desa pakraman), konversi lahan pertanian, analisis stakeholder, dualitas tata kelola lahan